Mediators between Yoga Practice and Psychological Well-Being: Mindfulness, Body Awareness, and Satisfaction with Body Image - Tihanyi, Benedek T.; Böőr, Petra; Emanuelsen, Lene; Köteles, Ferenc (European Journal of Mental Health, 2016)
Regular yoga practice was connected to higher levels of psychological well-being in cross-sectionaland longitudinal studies. However, the psychological mechanisms of this connection are stillunexplained. In the present cross-sectional questionnaire study, hypothesised mediating effects ofbody awareness, satisfaction with body image, and mindfulness were investigated. 203 healthyadults (183 females, mean age: 36.8 ± 10.03 years) practicing yoga at an advanced level wereinvolved in the study. Participants completed online questionnaires assessing body awareness(BAQ), dissatisfaction with body image (BIQ), mindfulness (MAAS) and well-being (WHO-5).Body awareness, body image dissatisfaction and mindfulness showed significant correlations withthe weekly frequency of yoga practice as well as with psychological well-being. Body awareness,body image and mindfulness mediated the connection between yoga practice and well-being. Inthe regression analysis, body image dissatisfaction and body awareness remained connected towell-being even after controlling for practice frequency, mindfulness, gender and age. Accordingto these results, body awareness, body image satisfaction and mindfulness are mediators of theconnection between yoga practice and well-being.